Briefing Gender Male Guppy Fish (Poecilia reticulata) Through Immersion Parent in Coconut Water Solution with Different Doses and Time - Mhd Sukrillah; Sukendi '; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The aims of the was study to determine the effect of immersion parent fish guppy pregnant using coconut water with different doses and time of the percentage of male fish seed production. Selected coconut water as a natural ingredient of synthetic hormone replacement 17α-methyltestosterone (MT) is commonly used for aligning the male fish. This research was conducted in June through September 2013 the Laboratory of Fish Hatchery and Breeding Faculty of Fisheries and Marine Science, University of Riau. This study used an experimental method with 12 treatments and 3 replications. This treatment uses doses of 0, 10, 25 and 45 ml of coconut water with immersion time 10, 20 and 30 hours. The results showed that no effect of coconut water toward the percentage of male guppy fish produced with the highest value at a dose of 10 ml were soaked for 20 hours which is 62.5%. Nevertheless, these results are still lower than the MT treatment (92.7%). At doses of 0 and 10 ml no effect on survival rate. However, at doses of 25 and 45 ml guppy fish survival rate decreases.Keywords: Briefing sex, coconut water, guppy fish, Poecilia reticulata